Contending with complexity: The role of evaluation in implementing sustainable natural resource management - Douthwaite, Boru; Delve, Robert J.; Ekboir, Javier M.; Twomlow, Stephen (2003)
Three case studies show that natural resource management (NRM) research aimed at sustainably improving the well-being of African small-holder farmers is complex, and that monitoring and evaluation (M&E) is an essential tool in coping with this complexity, supported by an ‘innovation systems’ view of the adoption process. In the case studies, researchers adjusted their activities and outputs on the basis of learning from M&E. Many of the insights came through identifying farmer innovations, which also proved a source of improvements to the respective technologies. Together, better understanding and iterative improvements made eventual widespread impact more likely. Farmers also learnt from M&E exercises and this learning facilitated adoption. The understanding of the early adoption process provided by M&E can provide a foundation for more plausible impact assessment.